Peningkatan Mutu Sdm Pokdarwis Melalui Sosialisasi Sport Massage Untuk Pertolongan Pertama Dalam Kecelakaan Di Desa Wisata Belitar Seberang - Azizatul Banat; Roni Syaputra; Dwinki Marta Pura; Oppa Chorindo; Randy Ardiansyah (Jurnal Dehasen Untuk Negeri, 2023)
Belitar Seberang Village, Sindang Kelingi District, Rejang Lebong Regency, Bengkulu Province is one of the tourist villages that received a tourism village award in 2022 from the Ministry of Tourism and Creative Economy. Belitar Seberang Tourism Village is also a fostered village of Dehasen University Bengkulu, and in the context of community service carried out by a team of lecturers from the Teaching and Education Faculty which is divided into several service groups including one of which is the lecturer service group which carries the title "Improving the Quality of Pokdarwis Human Resources Through Socialization of Sport Massage for First Aid in Accidents in the Belitar Seberang Tourism Village. Sport Massage is a touch that gives a feeling of security, comfort and warmth and freshness. Massage is intended to be given to anyone, including those who have experienced minor injuries that can be cured. In addition, massage also aims to have a good influence on pathological and post-traumatic conditions, improve blood circulation, normalize organ function, be useful in avoiding diseases and disorders that may occur and maintain, repair and eliminate fatigue. The socialization that discusses sports massage as first aid in an accident is intended to provide understanding and additional basic skills for the team of tourism village management groups as one of the knowledge and skills that really need to be owned by tourism village managers considering tourism is the goal of many people to visit and enjoy panoramic views of nature, but not all visitors are familiar with and understand tourist areas that are still natural with hills, so it is necessary to prepare a form of emergency services in case of minor accidents such as sprains/sprains, muscle cramps, etc. which will be assisted with massage therapy before receiving further treatment. With the socialization, it is hoped that there will be an increase in the quality of Pokdarwis human resources in providing emergency services for prevention and preparation in the event of a minor accident. In addition, if studied more diligently, sports massage can also be one of the tourist services for visitors who need relaxation or health therapy such as sports massage.